The javan green peafowl (Pavo muticus muticus) is a endangered bird species. They have big pressure to the population and the habitat. The fact that the birds are still exist on their local distribution. Behavior ecology of javan green peafowl is dealing with activities, mechanism and strategies of the birds in relation to their environment. The aimed of the study is to obtain data and information of ecological adaptation strategies through the behavior activities, mechanism and strategies of ja - JARWADI BUDI HERNOWO; ANI MARDIASTUTI; HADI SUKADI ALIKODRA; CECEP KUSMANA (Bogor Agricultural University, Indonesia, 2011)
The javan green peafowl (Pavo muticus muticus) is a endangered bird species. They have big pressure to the population and the habitat. The fact that the birds are still exist on their local distribution. Behavior ecology of javan green peafowl is dealing with activities, mechanism and strategies of the birds in relation to their environment. The aimed of the study is to obtain data and information of ecological adaptation strategies through the behavior activities, mechanism and strategies of javan green peafowl in-relation to their habitat types. Ad libitum sampling method was used on continuous recording every peafowl activities in relation with duration, frequencies mechanism and strategy were influenced by habitat type’s condition. Chi-squre test was used for statistical analysis to know different behavior has influenced by habitat types. The result shown that the javan green peafowl habitat typse has significant influenced on duration of the activities but not at the activities pattern. The walking during the feeding, select shading places or luxuriant trees close to feeding site, choosing tall trees or emergent trees close to open area as roost site, open area also road as display or dancing area, open area which grow shrubs as nesting site are javan green peafowl ecological behavior strategies. The mechanism and strategies of javan green peafowl behavior ecology are related to avoid from disturbance and to adapt their habitat type’s conditions.